SPIRRIG is required for BRICK1 stability and salt stress induced root hair developmental plasticity in Arabidopsis - Chi Zhang; Jingyu Zeng; Wenjuan Xie; Chuanseng Liu; Linyu Niu; Yanling Wang; Yali Wang; Muyang Shi; Jingxia Shao; Wenjia Wang; John Schiefelbein; Fei Yu; et al. (Stress Biology)
Abstract Developmental plasticity is critical for plants to adapt to constantly changing environments. Plant root hairs display dramatic plasticity under different environments and therefore play crucial roles in defense against environmental stressors. Here, we report the isolation of an Arabidopsis mutant, salinity over-sensitive mutant 1–1 (som1-1), also exhibiting root hair developmental defects. Map-based cloning and allelic analyses confirmed that som1-1 is a new mutant allele of SPIRRIG (SPI), which encodes a Beige and Chediak Higashi (BEACH) domain-containing protein. SPI has been reported to facilitate actin dependent root hair development by temporally and spatially regulating the expression of BRICK1 (BRK1), a subunit of the SCAR/WAVE actin nucleating promoting complex. Our living cell imaging examinations revealed that salt stress induces an altered actin organization in root hair that mimics those in the spi mutant, implying SPI may respond to salt stress induced root hair plasticity by modulating actin cytoskeleton organization. Furthermore, we found BRK1 is also involved in root hair developmental change under salt stress, and overexpression of BRK1 resulted in root hairs over-sensitive to salt stress as those in spi mutant. Moreover, based on biochemical analyses, we found BRK1 is unstable and SPI mediates BRK1 stability. Functional loss of SPI results in the accumulation of steady-state of BRK1.